2010
DOI: 10.1007/s10753-010-9258-4
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Activation Induces Nontolerant Inflammatory Response in Endothelial Cells

Abstract: In professional immune cells, Toll-like receptor 4 (TLR4) induces tightly regulated inflammatory response to avoid tissue damage via the induction of "endotoxin tolerance", which is a transient state of cell desensitization in response to lipopolysaccharide (LPS) restimulation after a prior LPS exposure. However, in endothelial cells, the regulation of TLR4-induced inflammation is not fully understood. In this study, we found that the gene transcripts for a lot of Toll-like receptors were expressed in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 21 publications
7
49
1
1
Order By: Relevance
“…Conversely, ECFCs are a highly differentiated population with a more limited role in immune responses and a less efficient production of IL-6. Nevertheless, ECFCs were still able o produce IL-6, suggesting their involvement in the formation of the cytokine milieu during the innate protective immune responses, as previously demonstrated for HUVECs [29].…”
Section: Discussionsupporting
confidence: 70%
“…Conversely, ECFCs are a highly differentiated population with a more limited role in immune responses and a less efficient production of IL-6. Nevertheless, ECFCs were still able o produce IL-6, suggesting their involvement in the formation of the cytokine milieu during the innate protective immune responses, as previously demonstrated for HUVECs [29].…”
Section: Discussionsupporting
confidence: 70%
“…In studies of the BBB, LPS binds Toll-like receptor 4 (TLR4) on leukocyte and endothelial cell surfaces, which results in the production of inflammatory cytokines, among them, TNF-alpha. Subsequent activation of myeloid differentiation factor 88 (MyD88) plays a critical role in the downstream effects of LPS, with resultant loss of endothelial tight junction integrity within endothelial cells of the brain (McGettrick and O'Neill 2010;Tauseef et al 2012;Wang et al 2011;Zhou et al 2006). These effector molecules activated by inflammation are relatively understudied elements of inner ear dysfunction.…”
Section: Systemic Inflammation Induced By Lps Causes Compromise Of Thmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4), a critical key factor in regulating innate immune response, induces remarkable expression of pro-inflammatory and pro-atherogenic cytokines in macrophages, VSMCs and endothelial cells when activated by binding to its ligand [15,16,17]. While TLR4 was originally described as a pattern receptor that recognizes lipopolysaccharide (LPS), recently, endogenous ligands have been found that are powerful TLR4 activators; examples are ox-LDL, fibronectin and heat shock protein 60 [18].…”
Section: Introductionmentioning
confidence: 99%